Educational Public Policies on English Language Teaching in Brazil Based on Neuroscience and Psychology of Human Development - de Souza Neves, Isabelle Lorena Alves; Neves, Felipe Oliveira (American Scientific Research Journal for Engineering, Technology, and Sciences, 2021)
The present study aims to reflect on the teaching of the English language in the initial grades of public and private network schools, it is considered that the offerings in public schools occur from the second phase of Elementary School, while in private school begins in Early Childhood Education. Through the qualitative method, it is sought to emphasize the relevance of the English Language and to point out the importance of insertion of this Language still in early childhood, to contribute to the fight against educational inequality in Brazil. It highlights in this bibliographic study questions pertinent to neuroscience as well as learning. The theoretical and methodological basis used in the research is based on theories of scholars such as Guyton and Hall, Watson, Skinner, Battro, Wallon and Vygotsky. The results showed that the early childhood learning process is flawed due to the moment the English Language is offered in public schools and the first step towards the reversion of this panorama may be through reflection with the attempt to change the current scenario.